An institutional survey for knowledge-based and self-awareness assessment in temporomandibular joint disorders among dental students - Sneha H Choudhary; Lata M Kale; Sunil S Mishra; Sonia Sodhi; Pooja B Muley; Narayan Dutt Pandey (Wolters Kluwer Medknow Publications, 2016)
Context: Temporomandibular joint disorders (TMDs) have been recognized as one of the most common causes of nondental orofacial pain. Various studies have been reported in literature regarding the relationship between prevalence of signs and symptoms of TMDs and gender, suggestive of female predilection; however, none of the studies have yet been reported to suggest the relationship between knowledge about temporomandibular joint (TMJ) and TMDs and self-awareness of its signs and symptoms. Aim: To find a relationship between the level of knowledge about TMJ and TMDs and self-awareness of its signs and symptoms. Settings and Design: This study was designed as an institutional survey. The study sample comprised 491 undergraduate and postgraduate (PG) students, consisting of 90 males and 401 females with age ranging between 18 and 32 years. Subjects and Methods: Two sets of questionnaire were distributed among the students. Statistical Analysis Used: Statistical analysis was performed with the help of Epi Info (TM) 3.5.3, descriptive statistical analysis, test of proportion, Chi-square test, one-way analysis of variance, Tukey's test, and knowledge index. Results: It was observed that there was a gradual increase in the level of knowledge about TMJ and TMDs and self-awareness of its signs and symptoms from the 1st year to PG students. Conclusions: A direct relationship exists between the level of knowledge about TMJ and TMDs and self-awareness of its signs and symptoms.